Identification and Mitigation of Risk Factors in the Implementation of the Probolinggo-Banyuwangi Toll Road Project Package 2 - Farid Anwar Amin; Andi Patriadi; Sajiyo Sajiyo (Journal of World Science, 2025)
This study focuses on identifying and mitigating risks associated with constructing the Probolinggo-Banyuwangi Toll Road Project Package 2, a vital segment of Indonesia's Trans-Java Toll Network. The background highlights the project's significance in enhancing regional connectivity and supporting economic growth alongside the challenges it faces from technical, managerial, financial, social, and environmental factors. This research aims to identify critical risks and develop effective mitigation strategies. The methodology involves data collection through interviews, surveys, and document analysis, prioritizing risks based on their probability and impact. Key findings reveal that delayed delivery, rising material prices, and lack of skilled labor are the most significant risks, demanding targeted mitigation strategies. The conclusion emphasizes the importance of implementing real-time risk monitoring systems, improving logistics coordination, and fostering stakeholder collaboration, particularly with government agencies. By prioritizing critical risks and developing comprehensive mitigation strategies, this research contributes valuable insights for managing complex infrastructure projects, ensuring project sustainability and success.